ANÁLISE DA COMUNICAÇÃO DA UNIVERSIDADE FEDERAL DO ESPÍRITO SANTO NO INSTAGRAM - Rezende, Mariana Simoes de (2020)
due to the popularization of the internet and its new possibilities, organizations need to adapt to new forms of communication, such as digital social networks. In this context are public universities, which are not always able to keep pace with these cha